ROLE OF BLOCKCHAIN IN AGRICULTURE - Singh, Harjinder (ShodhKosh: Journal of Visual and Performing Arts, 2023)
Blockchain technology has found applications across various sectors, and agriculture is no exception. Its role in enhancing food safety and streamlining transaction times is particularly noteworthy. As interest in Blockchain within the agricultural field grows, there’s a pressing need for a comprehensive overview. In response, we have conducted a systematic literature review (SLR) aimed at gathering all pertinent research on Blockchain technology in agriculture. This review identifies current research themes, key contributions, and the benefits of implementing Blockchain in agriculture. The paper provides a detailed examination of how blockchain technologies can facilitate traceability in the agri-food sector. It starts with definitions, adoption levels, tools, and the advantages of traceability, along with a concise overview of blockchain technology’s functionalities and benefits. Following this, an in-depth literature review explores the integration of blockchain into traceability systems. The discussion includes relevant existing commercial applications, while also highlighting the challenges faced and the future opportunities for Blockchain technologies in the agri-food supply chain.